Urban growth and urban infrastructure relations in Turkey - Turgut, S. (WIT PRESS, 2016)
Urban infrastructure relations are composed of the necessary transmission channels and facilities for a healthy and sustainable urban environment in terms of space and society in a settlement. The existence of a healthy and sustainable urban environment could only occur by reducing the problems of infrastructure relations to a minimum level, by abolishing these problems and taking precautions for the possible ones, and by analyzing these problems correctly. Correctly interpreting and classifying the data about infrastructure problems and taking them into consideration in the decision making process are as important as the data gathering process. The EU has determined four important strategic aims for sustainable urban development. One of these aims is the physical conditions, and infrastructure. In order to achieve these aims, a relation between urban infrastructures, urban planning decisions, and the construction of the superstructure must be established. The term infrastructure systems is commonly used for stating sewage projects, drinking water, electricity, natural gas, telephone, and telecommunication projects like cable TV. Infrastructure, symbolizing the development level of a country, is a topic that directly affects the health standards, the life standards, and the environment quality of people. Therefore, it is impossible to overlook infrastructure in creating a composed urbanization. In this paper, the urban infrastructure factor in Turkey will be elaborated in the context of urban growth, and particularly the planning process, in terms of the planning levels that are defined by law. The problems will be determined and will be opened to discussion.
Keywords: infrastructure; urban growth; urban management; Science & Technology - Other Topics; Environmental Sciences & Ecology; Urban Studies